Didáctico para el desarrollo del Pensamiento Matemático a través de la Resolución de problemas mediado por la Modelación Geométrica - Fonseca Vizcaya, Luz Marina (Universidad Antonio Nariño, 2024)
The development of mathematical thinking through a robust teaching and learning process allows for significant cognitive achievements in high school students. This process favors the acquisition of fundamental skills and abilities to understand, study and use mathematical concepts, establish connections and relationships between them to advance in problem solving in a systematic way. It also contributes to the construction of arguments to validate and represent objects abstractly, benefits the communication of mathematical ideas and stimulates creativity.